2016
DOI: 10.3390/ijerph13111095
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metabolic Genes in Blood Aluminum Concentrations of Jamaican Children with and without Autism Spectrum Disorder

Abstract: Aluminum is a neurotoxic metal with known health effects in animals and humans. Glutathione-S-transferase (GST) genes and enzymes play a major role in detoxification of several heavy metals. Besides a direct relationship with oxidative stress; aluminum decreases GST enzyme activities. Using data from 116 Jamaican children; age 2–8 years; with Autism Spectrum Disorder (ASD) and 116 sex- and age-matched typically developing (TD) children; we investigated the association of polymorphisms in three GST genes (GSTP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…Another important SNP in glutathione S-transferase superfamily is GSTP1 polymorphism, which has been suggested as contributing factor in ASD development years ago. As mentioned, the risk of ASD was observed in offspring of mothers with GSTP1 IleVal genotype 10 , as well as, in carriers of GSTP1 wild type genotype depending on blood manganese concentration or exposure to aluminum 11,15 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Another important SNP in glutathione S-transferase superfamily is GSTP1 polymorphism, which has been suggested as contributing factor in ASD development years ago. As mentioned, the risk of ASD was observed in offspring of mothers with GSTP1 IleVal genotype 10 , as well as, in carriers of GSTP1 wild type genotype depending on blood manganese concentration or exposure to aluminum 11,15 .…”
Section: Discussionmentioning
confidence: 80%
“…In recent years, significantly increased levels of lead and mercury, as well as a decrease of GST activity were noted in patients diagnosed with ASD, when compared to typically developed controls 14 . Moreover, another study has shown a possible interaction between GSTP1 polymorphism ( GSTP1 Ile/Ile genotype) and the effect of blood manganese concentration 11 , but also between GST polymorphisms and exposure to aluminum 15 . Available data on other GST genotypes are scarce, still GSTM1 null and GSTT1 null genotypes, alone or in combination with GSTP1 polymorphism, have been associated with risk of ASD 1618 .…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the GSTP1 gene using different genetic models, including the dominant (Val/* vs Ile/Ile) and the co-dominant models. For the GSTP1 polymorphism, we tested whether Hardy-Weinberg equilibrium expectations were met using the chi-square test in the TD control group (Rahbar et al, 2016; Rahbar et al, 2014d; Rahbar et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used conditional logistic regression (CLR) models to assess the association between ASD status (ASD case or TD control) and various exposure variables including genotypes for GSTP1, GSTM1, and GSTT1 (Rahbar et al, 2016; Rahbar et al, 2014d; Rahbar et al, 2015). Other variables included demographics and SES, parents’ education, and potential nutritional exposures.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2009, the research team at University of Texas Health Science Center at Houston (UTHealth), in collaboration with investigators at the University of the West Indies (UWI), have conducted two phases of an age‐ and sex‐matched case‐control study to investigate the role of the GST genes (e.g., GSTP1 ) and their potential interactions with five metals, lead (Pb), mercury (Hg), arsenic (As), cadmium (Cd), and manganese (Mn), in relation to ASD in Jamaica. Details on the recruitment and assessment procedures of this study have been reported previously (Rahbar et al., , , , , , , , ). So far, a significant gene‐environment interaction between GSTP1 and Mn was found when Mn was the only metal that was assessed (Rahbar et al., ).…”
Section: Application To the Epidemiological Research On Autism Spectrmentioning
confidence: 99%